Foreign Geographical Indications, Consumer Preferences, and the Domestic Market for Cheese. (7th August 2019) - Slade, Peter; Michler, Jeffrey D.; Josephson, Anna
Abstract: The protection of geographical indications (GIs) is an important feature of modern trade agreements. In the Canada‐European Union Comprehensive Economic and Trade Agreement (CETA), Canada agreed to stronger protections for GIs of European cheeses and other food products. Under this agreement, new Canadian producers can no longer label cheese as "feta" but instead must refer to it as "imitation feta, " "feta style, " or "feta type." We use a choice experiment to determine the effect of this agreement on Canadian cheese producers. We find that the effect of GI recognition varies depending on the terms used to label Canadian cheese and the information given to consumers. The results imply that policies that give greater latitude to food marketers will weaken the impact of GI recognition.